Evaluation of cabbage ( Brassica oleracea L. var. capitata ) Genotypes for compactness and internal tipburn resistance under rain shelter - Ningappa Kirasur (Department of Olericulture, College of Horticulture, 2016)
The experiment entitled “Evaluation of cabbage (Brassica oleracea L. var. capitata) genotypes for head compactness and internal tipburn resistance under rain shelter” was carried out in the department of Olericulture, College of Horticulture, Vellanikkara during the period from May to September 2015. The major objectives of the study were to identify compact genotypes with high yield for rain shelter cultivation, to identify genotypes with internal tip burn resistance, a calcium related physiological disorder and also to study the effect of calcium foliar application on the incidence of internal tip burn. Seven cabbage genotypes were evaluated with three different calcium foliar treatments (0%, 0.5% and 1.5%). All the cabbage genotypes showed significant difference with respect to qualitative and quantitative characters studied. Number of wrapping leaves, head length, head breadth, net head weight, head index, harvest index and head compactness directly contributed towards yield. The minimum number of wrapping leaves (8.60) was in genotype G 1 (NS 43) and the genotype G 8 (Saint) recorded the minimum number of non-wrapping leaves (7.70) . The genotype G 1 (NS 43) recorded maximum plant spread (50.70 cm), head length (12.91cm), head breadth (13.40 cm), net head weight (787.33 g) and gross head weight (1136.66 g). The genotype G 4 (F 1 Border 777) recorded the maximum head index (1.31), but harvest index was maximum for the genotype G 8 (69.60 %). All the genotypes formed very compact heads in all Ca foliar treatments, except G 1 (NS 43) which formed loose heads in C 2 (Ca 1.5 %) treatment, medium compact heads in control (C 0 ) and C 1 (0.5 %) treatments. All the genotypes produced conical heads except G 1 (NS 43) which produced round heads. The genotype G 5 (Green Voyager) recorded maximum yield of 6.40 kg per plot. Among the seven genotypes, only the genotype G 1 (NS 43) recorded slight tipburn incidence (4.16 %). Genotypes G 3 (Super Ball 50), G 4 (F 1 Border 777), G 6 (Mahy 118) and G 8 (Saint) were free from pest incidence and genotypes G 2 (Green Challenger), G 5 (Green Voyager) and G 6 (Mahy 118) were free from disease incidence.Effect of different levels of calcium foliar application and the interaction effect were non-significant in most of the characters. However the interaction G 4 C 0 recorded the lowest stalk length (5.25 cm) and interaction G 1 C 2 recorded the highest gross head weight (1365 g). The interaction G 1 C 2 recorded slight incidence of tipburn (1.78 %). There was no pest incidence in the interactions G 8 C 0, G 6 C 1, G 4 C 0 and G 3 C 1. The interactions G 5 C 0, G 2 C 0 and G 6 C 2 registered no disease incidence. Soil samples were collected from all the experimental plots before and after raising the crop. Soil samples were analysed for pH, organic carbon, available P, K, Ca, Mg, Fe and Mn content. There was no significant difference with respect to soil pH, organic carbon, available P, K, Ca, Mg, Fe and Mn content among the plots before and after raising the crop. Index leaf (recently matured wrapping leaf and head) samples were collected from internal tipburn susceptible genotype G 1 (NS 43) and high yielding, resistant genotype G 5 (Green Voyager). Plant samples were analysed for N, P, K, Ca, Mg, Fe and Mn content both in leaf and head. Here also there was no significant difference among genotypes for N, P, K, Ca, Mg, Fe and Mn content both in leaf and head samples. The foliar application of Ca increased leaf calcium concentration in both the genotypes. Maximum leaf Ca content was recorded in the interaction G 5 C 2 (1.20